Dinosaurs divorce : a guide for changing families - Brown, Laurene Krasny (New York : Joy Street Books, 1986)
Text and illustrations of dinosaurs introduce aspects of divorce such as its causes and effects, living with a single parent, spending holidays in two separate households, and adjusting to a stepparent.
Adult 530
Keywords: Separation (Psychology) -- Juvenile literature; Divorce -- Juvenile literature